Automated detection of velocity pulses in ground motions based on adaptive similarity search in response spectrum. Issue 149 (October 2021) - Tang, Yuchuan; Wu, Chenhao; Wu, Gang
Abstract: Ground motions with strong pulse-like features are of special concern for structural engineers. Detection and characterization of the pulse-like features are fundamental in seismic hazard analysis, ground motion selection/simulation, and structural analysis. From the perspective of earthquake engineering, a pulse-like feature in a ground motion is of significance only if it dominates certain structural response to the ground motion. In order to identify such kind of pulse-like features, the current study establishes the so-called response spectra associated with various velocity waveforms through dimensional analysis of structural response to a generic velocity pulse. The congruence and the shifts between the Π P V and the pseudo-velocity response spectra associated with identical velocity waveform allow automatic detection of velocity pulses through adaptive similarity search in bi-logarithmic spectrum curves. Following this approach, velocity pulses are detected and characterized in hundreds of historical ground motion records. The majority of the detection results are comparable to the velocity pulses identified through wavelet analysis in literature, while significant differences are noticed for a few cases. Further investigation shows our approach is able to capture the velocity pulse that retains the impulsive effect of the original ground motion on structures and thus provides a worthy supplement to the existing pulse identification methods. Highlights: Detecting and characterizing the velocity pulse that retains the impulsive effect of the originalnear-fault ground motion on structures. Congruence and shifting relationship of bi-logarithmic response spectrum curves associatedwith ground velocity inputs of identical waveform. Automatic and adaptive searching for subsequence-to-subsequence similarity between twoplanar curves that have a non-predetermined shift. Supplement and verification to previous pulse detection methods that are based on signalprocessing techniques.